Building Type, Housing Density, and Water Use: Denver Water Data and Agent‐Based Simulations. (24th May 2022) - Sampson, David A.; Quay, Ray; Horrie, Mitch
Abstract: This study examined simulated changes in total (and outdoor) water demand with increased dwelling units per unit area (DUUA) for seven building types (BTs) in the Denver Water service area. We utilized the Denver Water Demand Model — a spreadsheet tool that uses inputs such as BT, population, household size, number of units, etc. — to develop an "agent‐based" simulator to permit scenario analyses of future water use for different mixes of BTs. We examined household "movement" for new residents from lower density to higher density classifications. Increased residential density can be achieved through multiple pathways. For instance, a family could move from a large single‐family (LSF) unit to a single‐family home with a smaller lot footprint (SSF). Or, a family could move into a multi‐family housing development from a SSF. Our results suggest uneven, nonlinear efficiency gains in water use with increased density, depending on the specific BT movements. Simulation outputs indicate that the greatest gains in water savings per unit change in DUUA can be achieved with short movements over the lowest density classes (e.g., LSF to a SSF). In addition, results suggest that increasing irrigation efficiency (less water applied per unit area irrigated) may decrease total residential water demand by 5% to 25% over baseline; efficiency of irrigation may prove to be as effective, if not more, at reducing residential water demand as increasing housing density. Abstract : Research Impact Statement : Efficiency of irrigation may prove to be as effective, if not more, at reducing residential water demand as increasing housing density.